Web-based online bakery ordering system with QR code / Aida Afiqah Alias - Alias, Aida Afiqah (2021)
The project aims to develop a web-based ordering system to revolutionize the traditionally designed ordering system currently used in Najah Bakery of UiTM Cawangan Perlis. The traditional method used by most food and beverage industries is the traditional manual ordering system, where all works are done by manual labor. It involves a great deal of paperwork that is not effective and reliable. This leads to business problems due to the enormous amount of manual work in every business routine regarding human error. This web-based bakery ordering system is therefore designed to help the routine of business to manage and operate on a daily basis. Online Bakery Ordering System with QR Code was developed to ease the students and everybody in ordering the products without going to the bakery shop. The methodology chosen for this project is by using the ADDIE Model methodology, that consists of these phases; analysis, design, development, implementation, and evaluation. This is primarily done on an iterative basis, with a re-analysis assessment and further improvements to the design and development process. Using computerized systems in food ordering helps the developer engage with the target users in the implementation phase using the ADDIE Model, which can be used to analyze, assess, interpret, and learn about the system before implementing the final system effectively. Also, this project is evaluated the system by checking the system function through a Functionality Testing before the real user tested it during the User Acceptance Test (UAT). About 30 respondents were selected to use this system for both testings. The finding of this test agreed that the system is good to be used. At the end of the project, some recommendations for the future are also discussed based on the limitation identified throughout the project to provide possibilities for further improvement.